Europäischer Individualrechtsschutz in Parallelverfahren - Lipps, Gabriel (Mohr Siebeck, 2024)
In parallel proceedings, in principle the first court to be called upon will have priority in accordance with the Brussels 1a Regulation. Aside from that, the priority of the court which was determined by exclusive jurisdiction agreements takes effect in accordance with Article 31 Paragraphs 2-4 of the Brussels 1a Regulation. Gabriel Lipps studies in particular the scope, extension and supplementation of this regulation.
PublicationDate: 20240430
Keywords: allgemeine Rechtsgrundsätze -- forum shopping -- Ausschließliche Gerichtsstandsvereinbarung -- Kompetenzkonflikt -- Torpedoklage -- Justizgewähranspruch -- selbstlernende Algorithmen -- Internationales Privatrecht -- Zivilverfahrensrecht, Insolvenzrecht -- Ausländisches Recht, Rechtsvergleichung